2008
DOI: 10.1590/s0102-311x2008000700017
|View full text |Cite
|
Sign up to set email alerts
|

Hanseníase no Estado do Espírito Santo, Brasil: uma endemia em ascensão?

Abstract: This study provides a trend analysis of leprosy among patients in the State of Espírito Santo, Brazil, from 1980 Using temporal series statistical models, an upward trend was identified throughout the period in the overall detection rate (p < 0.05), with an apparent stabilization at the end of the period. We also observed an upward trend for the following periods: (i) 1980-1987 in the < 15 and ≥ 50-year age groups and for paucibacillary forms; (ii) 1988-1995 for the 15-19, 20-29, and ≥ 50-year groups and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
3
11
0
6
Order By: Relevance
“…The upward shift in detection rates seen in Aracaju is similar to the trend reported in other Brazilian studies [15][16][17][18][19] , but a steady decline is evident from 2003 onward. These results contrast with the pattern reported for states in the process of eliminating the disease as a public health problem, such as Paraná 20 and São Paulo 21 , which exhibited a pattern of steady decline in detection rates over the same time frame.…”
Section: Clinico-epidemiological Characteristics Of Casessupporting
confidence: 88%
See 1 more Smart Citation
“…The upward shift in detection rates seen in Aracaju is similar to the trend reported in other Brazilian studies [15][16][17][18][19] , but a steady decline is evident from 2003 onward. These results contrast with the pattern reported for states in the process of eliminating the disease as a public health problem, such as Paraná 20 and São Paulo 21 , which exhibited a pattern of steady decline in detection rates over the same time frame.…”
Section: Clinico-epidemiological Characteristics Of Casessupporting
confidence: 88%
“…Rates for the Vale do Jequitinhonha were found to exceed those State of Minas Gerais, where parameters for the region were responsible for sustaining the epidemic and contributed to its classification of high to very high 24 19 . Although other studies have shown similar slight increases in detection in children 25 or have pointed to a steady pattern over time 26 , a study in a historic series performed in Bahia is noteworthy.…”
Section: Clinico-epidemiological Characteristics Of Casesmentioning
confidence: 93%
“…Characteristic of the aforementioned situation, the State of Rio Grande do Sul, Brazil, has reached the goal of reducing its prevalence, and in 2008 presented a coefficient of 1.65 cases/100,000 inhabitants, which is lower than the coefficient found in Brazil 2,5 . In 2009, the State of Espírito Santo was the only state in the southeast of the country presenting high endemic levels, thus being categorized as a priority region for control programs of this disease 2,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of worldwide cases are concentrated in only six countries: India, Brazil, Nepal, Myanmar, Mozambique and Madagascar. Brazil registered about 36,000 new cases in 2009 and was the only country in the Americas that did not attain the prevalence goal of less than one case per 10,000 inhabitants, as proposed by the World Health Organization and accepted by the government in 1991 (Martelli et al 2002, Moreira et al 2008, DATASUS 2010.…”
mentioning
confidence: 99%